Analysis of Mathematical Connection and Communication Skills in Flat-Sided Solid Geometry Material Based on the Mathematical Skills of Grade VIII Students at SMP Negeri 12 Palu - Nadia Maulidina; Mustamin Idris; Muh. Hasbi; Nurhayadi Nurhayadi (Journal of Educational Sciences, 2026)
Mathematics is an important subject that emphasizes mastery of concepts, communication, and mathematical connections. Mathematical connection skills enable students to relate concepts to one another, to other fields of science, and to everyday life, while mathematical communication skills facilitate the delivery of mathematical ideas verbally, in writing, and visually. This study aims to analyze students' mathematical connection and communication skills in solving flat-sided solid problems based on their mathematical ability levels. The research used a descriptive qualitative approach with three students from SMP Negeri 12 Palu as subjects, each representing high, medium, and low ability levels. Data were collected through written tests and semi- structured interviews, then analyzed using the Miles and Huberman model through the stages of condensation, presentation, and conclusion drawing and data verification. The results showed that high-ability students were able to understand, connect, and communicate flat-sided shape concepts completely and systematically. Medium-ability students demonstrated sufficient understanding, although there were deficiencies in the consistent use of symbols and drawing conclusions. Low-ability students experienced difficulties in connecting concepts, solving problems, and conveying ideas accurately.